Schooling and `Skilling' of the Country's Youth Secondary Education in Four Indian States - MANABI MAJUMDAR (Economic and Political Weekly May 28-June 4, 2005, 2005)
Focusing on variations in secondary schooling across the states of Andhra Pradesh, Kerala, Maharashtra and Tamil Nadu, this paper makes the claims that we need to deal with the challenges of universal elementary education and the expansion of secondary schooling simultaneously, rather than in a gradual sequence. Except in a few educationally forward regions of the country, secondary participation remains highly restrictive because, a majority of young people - in particular from deprived communities - do not have access to secondary education. Decisions regarding virtually all school related activities are concentrated at the state level, to the relative neglect of sub-state level and school level actors. Vocational secondary education and `skilling' of adolescents have always received step-motherly policy attention. Interestingly, however, in the majority of the sample states, aided schools seem to have become reasonably accessible to disadvantaged groups, in sharp contrast to unaided schools. Hence there is a case for strengthening aided schools, as a potentially effective means of narrowing the gaps between the privileged youth and their disadvantaged peers.